Examining Cities’ Outdoor Spaces through the Lens of Children’s Rights - Elena Pagliarino; Maria Letizia Montalbano (Fuori Luogo)
The primary objective of this article is to instigate a discourse about the potential contribution of outdoor urban spaces to the complete fulfilment of post-pandemic childhood. The article focuses on the Italian context, but makes reflections that can be generalized to other European countries. The article originates from the observation that the rights of Italian children have been overlooked by the national political agenda during the Covid-19 pandemic. It considers, then, how this neglect should be seen not as an occurrence linked to the health crisis, but as a condition that has persisted for years and which the pandemic has only highlighted and exacerbated. The article examines a series of historically consolidated experiences and innovative practices developed during the pandemic in several European cities, featured by the objective of responding to the children’s rights to education, play, security, self expression, and to be listened through the use of cities’ outdoor spaces. Such inspirational case studies are firstly categorized according to the right to which they respond, following the International Convention on children’s rights, and then analysed following an interdisciplinary framework between environmental education and urban sociology. This analysis suggests that urban strategies should look at children both as beneficiaries and actors. The transformation of cities’ outdoor public and private spaces needs the integration of policy and action to overcome the fragmentation of initiatives that target specific urban sub-populations or cities issues. A whole-city approach which focuses on children’s development will deliver long-term benefits, affecting current and future generations, and contributing to build cities that are safe, healthy and inclusive for everyone.